Lives versus livelihoods? Perceived economic risk has a stronger association with support for COVID-19 preventive measures than perceived health risk - Nisa, Claudia F; Belanger, Jocelyn J; Faller, Daiane G; Buttrick, Nicholas R; Mierau, Jochen O; Austin, Maura M. K.; Schumpe, Birga M.; Sasin, Edyta M.; Agostini, Maximilian; Gutzkow, Ben; Kreienkamp, Jannis; Abakoumkin, Georgios; et al. (Springer Nature, 2021)
This paper examines whether compliance with COVID‑19 mitigation measures is motivated by wanting to save lives or save the economy (or both), and which implications this carries to fight the pandemic. National representative samples were collected from 24 countries (N = 25,435). The main predictors were (1) perceived risk to contract coronavirus, (2) perceived risk to suffer economic losses due to coronavirus, and (3) their interaction effect. Individual and country‑level variables were added as covariates in multilevel regression models. We examined compliance with various preventive health behaviors and support for strict containment policies. Results show that perceived economic risk consistently predicted mitigation behavior and policy support—and its effects were positive. Perceived health risk had mixed effects. Only two significant interactions between health and economic risk were identified—both positive.